2021
DOI: 10.1186/s13244-021-01084-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and imaging features of carcinosarcoma of the uterus and cervix

Abstract: Aim The purpose of our study was to analyze the clinical and imaging features of uterine carcinosarcoma (UCS) and cervical carcinosarcoma (CCS), and to explore the diagnostic and staging accuracy of computed tomography (CT) and magnetic resonance imaging (MRI) examinations. Methods 41 patients including 37 with UCS and 4 with CCS from July 2011 to September 2020 were enrolled in the study. Of the 37 UCS cases, 7 had CT images, 27 had MRI images, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The results showed that the probability of LNM in patients with an LN short diameter ≥ 10 mm was significantly higher than that in patients with an LN short diameter < 10 mm. However, judging lymph node metastasis only by shape and size will lead to some false negatives [ 26 ]. Eighty-nine patients in our cohort showed that the LN max was < 10 mm, but postoperative pathology confirmed that the lymph nodes were positive.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the probability of LNM in patients with an LN short diameter ≥ 10 mm was significantly higher than that in patients with an LN short diameter < 10 mm. However, judging lymph node metastasis only by shape and size will lead to some false negatives [ 26 ]. Eighty-nine patients in our cohort showed that the LN max was < 10 mm, but postoperative pathology confirmed that the lymph nodes were positive.…”
Section: Discussionmentioning
confidence: 99%
“…The staging method of the International Federation of Gynecology and Obstetrics or the Tumor, Node, Metastasis classification system should be used to interpret this malignancy because it is categorized as endometrial carcinoma. MRI has a 70% staging accuracy rate [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mass showed a low signal on MRI in T1WI, a slightly high signal in fat-saturated T2WI, and nodular low-signal features in all sequences, suggesting iron-containing heme deposits with inhomogeneous mild enhancement. CT and MRI imaging can reveal the size, shape, location, internal changes such as necrosis and bleeding, and invasion of surrounding muscles and bones[ 15 ]. Since MGCTTS has an apparently high metastatic propensity[ 4 ], a whole-body PET/CT examination can play an important role in the evaluation of distant metastases comprehensively, which can help in the staging and early detection of metastases.…”
Section: Discussionmentioning
confidence: 99%